The Effect of Sharia Compliance on Customer Loyalty Through Customer Satisfaction as a Mediating Variable at Bank Syariah Indonesia in Surabaya City - Rahmatika, Febrina; Nurafini, Fira; Ridlwan, Achmad Ajib; Indrarini, Rachma (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Bank Syariah Indonesia (BSI) is the largest Islamic financial institution in Indonesia, which still faces issues related to customer doubts regarding sharia compliance, particularly in terms of contract transparency, product conformity, and consistency in implementing sharia principles. Additionally, customer satisfaction is not yet optimal, especially in service quality and digital services, which impacts the relatively weak level of customer loyalty. This study aims to analyze the effect of sharia compliance on customer satisfaction and customer loyalty, as well as the role of customer satisfaction as a mediating variable among BSI customers in Surabaya City. This study employs a quantitative method using purposive sampling with 130 respondents. Data analysis was conducted using Partial Least Square – Structural Equation Model (PLS-SEM). The results indicate that sharia compliance has a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty and is able to mediate the relationship between sharia compliance and customer loyalty.